ANALISIS IMPLEMENTASI AKUNTANSI PEMBIAYAAN MUSYARAKAH BERDASARKAN PSAK NO 406 PADA BPRS HIK PARAHYANGAN CABANG CILEUNYI - Tantri Saraswati; Gina Sakinah (Jurnal Riset Multidisiplin Edukasi, 2025)
This research aims to analyze the implementation of musyarakah financing accounting based on PSAK No. 406 at BPRS HIK Parahyangan Cileunyi Branch. The research method used is a case study with a qualitative approach through primary and secondary data collection. Research data obtained from interviews with relevant parties and documentation in the form of published financial statements at BPRS HIK Parahyangan. The results showed that BPRS HIK Parahyangan Cileunyi Branch has implemented musyarakah financing accounting in accordance with PSAK No. 406. This can be seen from the recognition, measurement, presentation, and reporting of musyarakah transactions carried out by BPRS HIK Parahyangan Cileunyi Branch has followed the applicable PSAK and POJK. This research contributes to improving the understanding of sharia accounting practices, especially musyarakah financing in Islamic banking.